In the Heights : finding home - Miranda, Lin-Manuel, 1980-; Hudes, Quiara Alegría; McCarter, Jeremy, 1976- (Random House, 2021)
Lin-Manuel Miranda gives readers an extraordinary inside look at "In the Heights," his breakout Broadway debut, written with Quiara Alegría Hudes, soon to be a Hollywood blockbuster. Miranda offers untold stories, perceptive essays, and the lyrics to his songs. Features newly commissioned portraits and never-before-seen photos from backstage, the movie set, and productions around the world.